COMPARATIVE ANALYSIS OF JOKES AND OTHER GENRES OF LAUGHTER - Temirova, Feruza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
This article covers jokes and other funny genres. The author conducted a comparative analysis of a number of comedy genres, paying attention to their common and different aspects. The article’s main goal is to reveal that the joke is the most popular and viable genre in literature, as well as to show the importance of humor in journalism, drama and folklore. Each comic genre is explained separately and analyzed with examples. When analyzing each comic genre, the stages of its development from the first to the modern period are indicated, and information is given about representatives of Uzbek and world literature and their works that contributed to the development of these genres. The article reflects historical and modern examples of comic genres in a harmonious state. By comparing all comic genres, their similar characteristics and differences with the joke genre are shown. At the end of the article, the genre of the anecdote is examined in more detail, and a conclusion is drawn showing the importance of the anecdote in literary criticism. The article uses encyclopedic dictionaries, scientific publications and scientific articles. The examples provide examples of journalistic literature of the XX century.